A comprehensive study of the status and needs of national productivity organisations and the Asia productivity organisation - Mann RS (Asian Productivity Organisation, 2015)
The objective of this project was “To assist the Asian Productivity Organisation (APO) and National Productivity Organizations (NPOs) undertake a Needs Assessment to enable effective productivity-related strategies and programs to be developed and implemented at a National and APO-wide level”. The research was commissioned by the APO Secretariat and officially started on 18 February 2014 and concludes with the publication of this report on 5 June 2015. This report had the input of 16 NPOs (Bangladesh, Cambodia, Fiji, India, Indonesia, Iran, Lao, Malaysia, Mongolia, Nepal, Pakistan, Philippines, Republic of China, Sri Lanka, Thailand and Vietnam). A Chief Expert (supported by 7 researchers) and 16 National Experts coordinated the research and analysed the data provided by 372 staff, 390 customers and 130 NPO partners. Data was obtained on Country Trends, NPO Strategy, Systems and Services, NPO Performance Results, NPO SWOT Analysis and APO Strategy and Assistance. The results reflect the diversity of APO members. For example, the number of staff employed by NPO members varied from 16 in Nepal and Mongolia to 670 people in Sri-Lanka. Malaysia had the most training course attendees in 2013 with 130,517 people trained whilst some countries recorded less than 20 people trained. Some NPOs were almost 100% government funded whilst others received no government funding. Whilst the NPOs all had specific challenges and opportunities there was agreement with the APO’s current vision and mission, and most indicated that “Training courses, Technical expert services, Development of demonstration companies / organizations and In-country programs” had the most impact. The report provides many recommendations to assist the APO and NPOs such as encouraging more best practice sharing on institutional strengthening and capability building (to share strategies, organizational structure, infrastructure, funding models, staffing levels/ratios and approaches to governance, leadership, human resources, customer focus, operations and systems, and measurement, analysis and knowledge management) and on service delivery (to share success stories on how productivity-related services are being delivered). For both the APO and NPOs more needs to be done to raise the profile of productivity including simple steps such as the improved use of social media and improving the design and content of NPO websites. The report endorsed the need for an APO Roadmap which has a clear strategy and targets. Currently, 3 or more APO members are in the top 20 countries for 10 of 18 reputable international performance metrics but none were in the top 20 for Labour Productivity. Clear stretch targets for key performance metrics can help the APO to develop appropriate strategies and obtain alignment of NPO strategies. Some NPOs require help in developing their own National Plans and Roadmaps. This report contains a wealth of information which can be used as a reference guide and for benchmarking purposes for many years to come.